Analysis on the dynamic mechanism of Acetes aggregation near a nuclear power cooling water system based on the Lagrangian flow network - Lou, Qi; Zhang, Xueqing; Xiang, Xusheng; Yu, Fan; Xiong, Ying; Li, Zhengyan (Frontiers in Marine Science, 2023)
The outbreak of nuclear power cooling water system (NPCS) disaster-causing organisms has become more frequent, causing huge economic losses. Therefore, it is necessary to understand the aggregation mechanism of disaster-causing organisms for the risk prevention and control of NPCS. Hence, this study applied the Lagrangian flow network (LFN) to analyze the aggregation mechanism of Acetes near NPCS, as such a complex network can describe the interconnections between massive nodes and has already been used for modeling complex nonlinear systems, revealing how the mechanisms of such novel processes emerge. In this study, the degree and probability paths in the network were used to reveal the transport pathway and aggregation area of Acetes. The experimental results highlighted that the sea area of the nuclear power plant is the key node with a large in-degree of the LFN, where the material easily accumulated. The Acetes near the NPCS mainly originated from the east along two critical paths. Overall, this study demonstrates that the LFN is a feasible approach to predicting the transport and the accumulation of the NPCS disaster-causing plankton.